Exploratory study on the characteristics of charitable donors in Australia - Lwin, Michael (School of Marketing, Curtin Business School, 2010)
Decline in government funding for charities led to a new era of marketing for charities in Australia. Operating like businesses, charities contest for a share of the $5.7 billion of household donations. The research investigates the characteristics of Australian charitable donors. Limited empirical research is available in this field and the paper replicates Schlegelmilch et al. (1997) research to develop a better understanding of Australian donors' demographics, psychographics and perception of charities. Findings show donors are more likely to be older individuals with higher income, who perceive themselves to be generous and financially secured. They have favourable attitude towards national and international charities, and they are more accepting towards higher administration costs. The research provides a clearer profile of the donor's market. Thus donors could be targeted more effectively. The research also identifies major differences between Schlegelmilch et al.'s (1997) British research. The findings indicate that the characteristics of donors differ between each country and more exploration is needed in this field.